The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.02.01.22270003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between brain imaging and polygenic scores of mental health and educational attainment in children aged 9-11

Abstract: Background: Psychiatric disorders are highly heritable and polygenic, and many have their peak onset in late childhood and adolescence, a period of tremendous changes. Although the neurodevelopmental antecedents of mental illness are widely acknowledged, research in youth population cohorts is still scarce, preventing our progress towards the early characterization of these disorders. Methods: We included 7,124 children (9-11 years old) from the Adolescent Brain and Cognitive Development Study to map the asso… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
1
3
0
Order By: Relevance
“…We also found norm-violating behavior to be associated with L1 dev and SA dev . This is in line with a study of 7124 children aged 9-11 years from the ABCD study reporting a negative association between externalizing problems and surface area (Fernandez-Cabello et al, 2022). For SA dev we also found evidence for an association with the anxiety domain score.…”
Section: Associations Between Brain Deviations and General And Domain...supporting
confidence: 92%
See 1 more Smart Citation
“…We also found norm-violating behavior to be associated with L1 dev and SA dev . This is in line with a study of 7124 children aged 9-11 years from the ABCD study reporting a negative association between externalizing problems and surface area (Fernandez-Cabello et al, 2022). For SA dev we also found evidence for an association with the anxiety domain score.…”
Section: Associations Between Brain Deviations and General And Domain...supporting
confidence: 92%
“…While the current associations between modalities were weak, there is wide support for the benefits of combining multiple MRI modalities when studying brain development, aging, and disease (Fernandez-Cabello et al, 2022;Groves et al, 2012;Rokicki et al, 2021;Smith et al, 2020). Combining measures increases sensitivity to age and improves discrimination accuracy for common disorders of the brain (Doan et al, 2017;Rokicki et al, 2021) and has been shown to boost gene discovery for brain imaging features (van der Meer et al, 2020),.…”
Section: Normative Deviations Across Different Modalities Show Little...mentioning
confidence: 99%
“…The effect sizes were moderate and comparable to previous studies using other neuroimaging-based outcomes to study the associations between brain structure and puberty (Vijakumar et al, 2021). Brain development during adolescence is likely shaped by an interaction of genetically programmed age-related changes, biological processes, and fluctuating environmental pressures (Fernandez-Cabello et al, 2022; Ferschmann et al, 2022). Combined with previous findings, our study shows that the effects of puberty are non-negligible and should be considered an influencing factor when studying adolescent brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Brain development during adolescence is characterized by a highly coordinated sequence of both progressive (cell growth and myelination) and regressive (synaptic pruning) processes (Paus et al, 2008), observable as nonlinear trajectories of cortical thinning and white matter volume increase in relation to chronological age (Blakemore & Choudhury, 2006). The neurodevelopmental progress is most likely shaped by a complex interplay of genetic factors, changes in biological processes, and new environmental pressures (Fernandez-Cabello et al, 2022; Ferschmann et al, 2022). In parallel to brain development, adolescence is a period of drastic changes in physiological processes and body composition during puberty.…”
Section: Introductionmentioning
confidence: 99%